The Institutional Arabic Language Curriculum Based on Outcome-Based Education in Islamic Higher Education Institutions - Isop Syafei (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the urgency of implementing Outcome-Based Education (OBE) in the development of the institutional Arabic language curriculum at Islamic Higher Education Institutions (PTKI), identify relevant learning outcomes for students, design a curriculum model in accordance with higher education standards and OBE principles, and evaluate the challenges and opportunities of its implementation within PTKI’s scientific and institutional context. A descriptive qualitative approach was employed to analyze the OBE-based institutional Arabic language curriculum at PTKI. Primary data were obtained through interviews and observations, while secondary data were derived from documents and literature. Miles and Huberman’s interactive analysis model was applied with source triangulation, producing a valid, applicable curriculum model aligned with higher education standards. The findings indicate that the implementation of OBE in the Arabic language curriculum at PTKI is urgent, as the current curriculum remains normative, lacks applicability, and is not measurable. Students require communicative, academic, professional, and Islamic-oriented competencies to strengthen global competitiveness. An ideal OBE-based curriculum should integrate institutional vision, specific outcomes, competency-based structure, and authentic evaluation. Despite challenges such as limited lecturer competence, facilities, and paradigm resistance, opportunities emerge through national regulations, digitalization, global demand, and international collaboration.